2017
DOI: 10.1083/jcb.201604117
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of α-, β-, and γ-actin in axon growth and collateral branch formation in motoneurons

Abstract: α-, β-, and γ-actin differentially regulate cytoskeletal dynamics and stability in axons of motoneurons. Locally translated α-actin contributes to stable actin filaments in axonal branches, whereas β- and γ-actin give rise to highly dynamic filaments that modulate growth cone dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 90 publications
(131 reference statements)
2
64
0
Order By: Relevance
“…C9ORF72 modulates the activity of the small GTPases, resulting in increased activity of LIM kinases 1 and 2 and regulation of axonal actin dynamics (Sivadasan et al, 2016). Various actin isoforms are expressed in primary mouse MNs, and their transcripts have been observed to be translocated into axons (Moradi et al, 2017). It is proposed that short hairpin RNA-mediated depletion of α-actin reduces axonal filopodia dynamics and disrupts collateral branch formation in developing MNs (Moradi et al, 2017).…”
Section: Aberrant Axonal Branchingmentioning
confidence: 99%
“…C9ORF72 modulates the activity of the small GTPases, resulting in increased activity of LIM kinases 1 and 2 and regulation of axonal actin dynamics (Sivadasan et al, 2016). Various actin isoforms are expressed in primary mouse MNs, and their transcripts have been observed to be translocated into axons (Moradi et al, 2017). It is proposed that short hairpin RNA-mediated depletion of α-actin reduces axonal filopodia dynamics and disrupts collateral branch formation in developing MNs (Moradi et al, 2017).…”
Section: Aberrant Axonal Branchingmentioning
confidence: 99%
“…In fibroblasts, knockdown and over-expression of β-actin reduces and enhances cell motility (Bunnell et al, 2011;Peckham et al, 2001), respectively, whereas γ-actin is not required for migration (Bunnell and Ervasti, 2010). In motor neurons, knockdown of β-actin reduces growth cone size and motility, whereas γ-actin-depleted neurons have normal axonal outgrowth, but display a reduction in axonal filopodia dynamics (Moradi et al, 2017). β-actin has also been found to be the more prevalent isoform in the G-actin pool (Kapustina et al, 2016), and β-actin knockouts in mouse embryonic fibroblasts have been shown to lead to decreased ratios of G-to F-actin (Bunnell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to stress that the observed functional distinctions between the isoforms are general trends (Flamholz et al, 2014) and, to some degree, the actin isoforms can compensate for each other. This is evidenced in experiments showing an upregulation of αand γ-actin in response to β-actin depletion (Moradi et al, 2017), or the downregulation of endogenous βand γ-actin genes in response to exogenously expressed γ-actin (Lloyd et al, 1992) to maintain overall cellular actin levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these RNA-seq data sets, as well as others now emerging (Rotem and others 2017), will bring new perspectives on how mRNA transport varies between different neuronal types, different physiological conditions, and disease states (Figure 1). For example, Moradi et al (2017) recently showed that axonally translated γ- and α-actin regulate different growth morphologies than β-actin in motor axons, while γ-actin mRNA is excluded from sensory and cortical axons (Moradi and others 2017). …”
Section: Introductionmentioning
confidence: 99%